1990
DOI: 10.1136/hrt.63.4.215
|View full text |Cite
|
Sign up to set email alerts
|

Functional importance of the long axis dynamics of the human left ventricle.

Abstract: The role of longitudinally and circumferentially oriented fibres in left ventricular wall motion was examined by digitising echocardiograms of the mitral ring (whose motion reflects long axis change) and of the standard minor axis in 36 healthy individuals, 36 patients with coronary artery disease, 16 with left ventricular hypertrophy, 44 with mitral valve disease (24 of whom had undergone mitral valve replacement). In the controls long axis shortening significantly preceded minor axis shortening (mean (1 SD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
188
1
5

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(201 citation statements)
references
References 18 publications
7
188
1
5
Order By: Relevance
“…37 A probable explanation is that patients with LV hypertrophy and normal short axis shortening, in addition to a reduced long axis shortening, also have a reduced circumferential shortening measured from the mid-wall, indicating myocardial dysfunction. 38,39 Thus, AV-LA/AV-mean may be a valuable measure of diastolic function in subjects with a normal LV mass, but is less suitable than other indices used in this study for the evaluation of diastolic function in subjects with LV hypertrophy.…”
Section: Discussionmentioning
confidence: 93%
“…37 A probable explanation is that patients with LV hypertrophy and normal short axis shortening, in addition to a reduced long axis shortening, also have a reduced circumferential shortening measured from the mid-wall, indicating myocardial dysfunction. 38,39 Thus, AV-LA/AV-mean may be a valuable measure of diastolic function in subjects with a normal LV mass, but is less suitable than other indices used in this study for the evaluation of diastolic function in subjects with LV hypertrophy.…”
Section: Discussionmentioning
confidence: 93%
“…The studies of ventricular fiber architecture have revealed a complex disposition of the myocardial fibers, with the predominance of a circumferential orientation for the middle muscle layer and a longitudinal disposition of the muscle fibers at the subendocardial level 18 . The importance of the longitudinal contractility has been demonstrated in several echocardiographic studies, both for the analysis of the systolic function, and also for the assessment of ventricular relaxation 19 . Of the methods used, Doppler tissue imaging has a great potential for the study of longitudinal contractility.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in Sw1 along the long axis contributes to spherical changes in the LV cavity during isovolumic contraction phase [23], and therefore a decrease in this peak velocity can be useful in the early diagnosis of impaired contractility in elderly individuals with normal LV pump function [24,25]. With respect to the TDI findings during early systole, Zamorano et al [26] simultaneously recorded M-mode color TDI and LV-aortic-left atrial pressures, and reported that there was a good correlation between the time interval assessed hemodynamically and that based on the velocity interface obtained with M-mode color TDI during the isovolumic contraction phase.…”
Section: Systolic Functionmentioning
confidence: 99%